2006
DOI: 10.1074/jbc.m605040200
|View full text |Cite
|
Sign up to set email alerts
|

CD47 Is Necessary for Inhibition of Nitric Oxide-stimulated Vascular Cell Responses by Thrombospondin-1

Abstract: CD36 is necessary for inhibition of some angiogenic responses by the matricellular glycoprotein thrombospondin-1 and is therefore assumed to be the receptor that mediates its anti-angiogenic activities. Although ligation of CD36 by antibodies, recombinant type 1 repeats of thrombospondin-1, or CD36-binding peptides was sufficient to inhibit nitric oxide (NO)-stimulated responses in both endothelial and vascular smooth muscle cells, picomolar concentrations of native thrombospondin-1 similarly inhibited NO sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
286
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 249 publications
(306 citation statements)
references
References 56 publications
18
286
0
2
Order By: Relevance
“…Although engaging CD36 is sufficient to inhibit NO signaling as well as VEGF-induced cGMP formation, we subsequently found that CD36 is not necessary for the same activity of intact TSP1 (21,22). Rather, we found that the TSP1 receptor CD47 is necessary and sufficient for the anti-angiogenic signal elicited by picomolar concentrations of TSP1.…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…Although engaging CD36 is sufficient to inhibit NO signaling as well as VEGF-induced cGMP formation, we subsequently found that CD36 is not necessary for the same activity of intact TSP1 (21,22). Rather, we found that the TSP1 receptor CD47 is necessary and sufficient for the anti-angiogenic signal elicited by picomolar concentrations of TSP1.…”
mentioning
confidence: 57%
“…8A). This could be explained by the ability of CD47 signaling to inhibit NO signaling in vascular cells at the level of sGC (22). In this case some of the inhibition of myristate signaling by TSP1 seen in Fig.…”
Section: Thrombospondin-1 Inhibits Myristate Uptake Via Cd36mentioning
confidence: 99%
See 2 more Smart Citations
“…19 Preclinical studies also suggest that an increased inflammatory response, cell adhesion, 20,21 and pathologic reactive oxygen species (ROS) production 22 contribute to SCD-associated vasculopathy. Interestingly, the proadhesive protein thrombospondin 1 (TSP1) was recently reported to inhibit NO signaling 23,24 while promoting PAH in preclinical models 25 and to be upregulated in SCD patient plasma. 26 Although studies have documented the hemodynamics and outcomes of SCD-associated PAH and interrogated the systemic vascular function of these patients, there have been no human studies directly evaluating the pulmonary vasculature.…”
Section: Introductionmentioning
confidence: 99%